La “Mostra Giottesca” (1937). La genesi e il progetto di allestimento di un’esposizione d’arte antica per il “riconoscimento della ‘rivelazione’ nel processo creativo” - Cattabriga , Ilaria (Lo sguardo rinnovato, 2026)
The contribution aims to analyze the “Giottesca Exhibition” of 1937 to reconstruct its scientific foundation, which distinguished it from the propagandistic and popularizing purposes of other coeval exhibitions, and to understand the reasons why the scientific soul of the exhibition, Mario Salmi, called it “an exhibition implemented by scholars and for scholars.”It is intended to pursue this objective by addressing the genealogical study of the event within the broader framework of the exhibitions mounted in Italy in the period between the two world wars, in order to understand how and why, on the one hand, even “Giottesca”, during the Fascist twenty-year period and in the vivid city situation ignited by the local cultural activities, became an interpreter of the propagandistic aims of national cultural primacy and of Italian specificities, and on the other, how, unlike other interventions, it radically revolutionized the way of exhibiting according to its own scientific ambitions through an innovative ordering of the works of art and thanks to the exhibition design by Giovanni Michelucci, Giuseppe Giorgio Gori and Mario Chiari. Using this key, an attempt will be made to define according to what parameters it became an innovative device for knowledge of works of art and a reference for Second Twentieth-Century stagings.